Nanowatt power management circuit design AIoT device - Ho, Yeung Ken (Nanyang Technological University, 2023)
The rise of the Internet of Things (IoT) and the increasing usage of artificial intelligence tools have led to a significant surge in demand for IoT devices. This has brought about new challenges for designers, as they strive to optimize battery life while maintaining peak performance. As a result, power management units are crucial to regulate the voltage of the power supply, allowing IoT devices to operate more efficiently and with a longer battery life. This research project showcases the design of a hysteretic voltage mode control buck converter for low power IoT applications using TSMC 22nm CMOS technology process. The proposed converter incorporates zero current detection and operates with low power consumption. The operating input supply voltage ranges from 1.5V to 3.0V and the converter can provide a stable regulated output voltage of 0.9V with a maximum output load current of 100mA. At 100mA load conditions, the buck converter has a peak efficiency of 93.1%, an output voltage ripple of 29mV, and a switching frequency of 1.95MHz. Under light load conditions, the converter consumes a quiescent current of 3.93 A. The designed converter is suitable for low-power IoT applications, such as security systems, smart homes, and wearable devices, where a reduced form factor and low power consumption are desirable.